2013
DOI: 10.1037/a0028444
|View full text |Cite
|
Sign up to set email alerts
|

The embodiment of focus: Investigating the impact of leaning behavior on our cognitive state and other's perception of our cognitive state.

Abstract: The emerging literature on embodied cognition highlights the role that the body plays in cognitive and affective processes. We investigated whether different body postures, specifically leaning postures thought to reflect different states of cognitive focus, can impact cognitive focus and task performance. In three experiments we confirmed that different postures are perceived reliably by others to convey distinct and different states of cognitive focus. However, the individuals who actually adopted the postur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In other words, these spontaneous natural behaviours can make the embodied nature of cognition visible (Chandrasekharan et al, 2010;Hostetter & Alibali, 2008). Critically, we argue that this is unlikely to be limited to gesture (Chisholm et al, 2013;Risko et al, in press). Here we expand this notion of natural behaviour providing a window into the embodied nature of cognition to a novel contextteleoperation.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In other words, these spontaneous natural behaviours can make the embodied nature of cognition visible (Chandrasekharan et al, 2010;Hostetter & Alibali, 2008). Critically, we argue that this is unlikely to be limited to gesture (Chisholm et al, 2013;Risko et al, in press). Here we expand this notion of natural behaviour providing a window into the embodied nature of cognition to a novel contextteleoperation.…”
mentioning
confidence: 67%
“…a ready window into the relation between brain, body, and world. This approach has been used successfully in a number of different domains (e.g., Chisholm, Risko, & Kingstone, 2013;Goldin-Meadow, 2005;Kirsh, 1995;Risko & Kingstone, 2011;Risko, Medimorec, Chisholm, & Kingstone, in press;Schwartz & Black, 1996;Vallee-Tourangeau & Wrightman, 2010). In the present investigation, we apply this approach in the context of teleoperation in order to provide new insights into the representation of remote actions.…”
mentioning
confidence: 99%
“…This strategy (e.g., forcing individuals to engage in a behavior, restricting that behavior) can provide critical information regarding a given behavior's contribution (or lack thereof) to cognitive function (e.g., Alibali et al., ; Chandrasekharan et al., ; Chu & Kita, ; Goldin‐Meadow et al., ). This strategy has been used in previous work investigating natural behavior (e.g., Carlson et al., ; Cary & Carlson, , ; Chisholm, Risko, & Kingstone, ; Goldin‐Meadow et al., ). In addition, restriction of physical rotation is, of course, the standard procedure in work on rotated object identification.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent series of experiments Chisholm et al (2013) demonstrated that leaning forward and back are viewed consistently as indicating focused and unfocused attentional states. Another overt cue commonly used to infer another person's attentional state is fidgeting (Galton, 1885; Mehrabian and Friedman, 1986; Gligoric et al, 2012; Carriere et al, 2013).…”
Section: Fidgetingmentioning
confidence: 99%